The significance of home reading developing spoken language skills in the third year - Čepaitė, E. (Psichologija, 1963)
The article deals with some home reading moments using third-year students' spoken language skills.Among other teaching objectives, home reading (ideological and aesthetic education, expansion of intellectual horizons, etc.) checks can and should be used to ensure the quality of home reading and spoken language skills.The paper analyzes how this works and gives specific methodological guidance on how to develop learners' spoken language skills and check home reading assignments.
Keywords: home reading and spoken language skills.